2013
DOI: 10.5144/0256-4947.2013.124
|View full text |Cite
|
Sign up to set email alerts
|

Importance of viral pathogens in children with acute gastroenteritis in the south of Iran

Abstract: BACKGROUND AND OBJECTIVESDifferent types of viruses are the leading cause of acute diarrhea among infants and young children worldwide. Epidemiological surveillance of viral agents is critical for the development of effective preventive measures, including vaccines. This study aimed to determine the prevalence of the four major enteropathogenic viruses—rotavirus, norovirus, adenovirus and astrovirus—in children over 7 years of age.DESIGN AND SETTINGA cross-sectional descriptive study conducted on stool specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
5
9
0
Order By: Relevance
“…We found HAdV in around 5% of children with acute gastroenteritis. Our findings were consistent with the detection rate of HAdV among acute gastroenteritis cases in earlier studies in Iran and other countries, which ranged from 2% to 9% and 1% to 31%, respectively. Three species and five types of HAdV were detected to be circulating during the study period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found HAdV in around 5% of children with acute gastroenteritis. Our findings were consistent with the detection rate of HAdV among acute gastroenteritis cases in earlier studies in Iran and other countries, which ranged from 2% to 9% and 1% to 31%, respectively. Three species and five types of HAdV were detected to be circulating during the study period.…”
Section: Discussionsupporting
confidence: 92%
“…In Iran, previous studies from 2002 to 2016 have been reported the prevalence of HAdV ranging from 2% to 9% among children, while AdV‐40 and AdV‐41 have been the most predominantly reported circulating types . Moreover, few reports have shown that AdV‐41 was the dominant type associated with acute gastroenteritis among children, which were similar to the findings of other studies .…”
Section: Introductionsupporting
confidence: 85%
“…Similar results are reported from a few other countries[33,42,43,67]. New GII.4 variants have been reported to emerge with unusual spring/summer seasonality[52], along with a total increase in wintertime disease in Europe.…”
Section: Discussionsupporting
confidence: 85%
“…Regionally, in the Middle East and North Africa (MENA), several studies have recently assessed the prevalence of NoV among hospitalized children aged < 5 years (hospitalized due to signs of acute gastroenteritis). These studies were performed on a variable sample size in Egypt[30], Israel[31,32], Iran[33], Jordan[34], Kuwait[35], Libya[36,37], Morocco[38], Tunisia[39,40], Turkey[41-45] and Yemen[46]. NoV was detected in stool samples of 6%-30% of hospitalized children aged < 5 years, with GII.4 and GII.3 predominantly reported in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this current work, we report on the clinical, epidemiological, and molecular characterizations of NoV infections among children suffering with AGE in Qatar between June 2016 and June 2018. Several studies from the MENA region had evaluated the prevalence of NoV in pediatric population, including studies from Libya [35,36], Israel [37,38], Jordan [39], Yemen [39], Egypt [40], Tunisia [41,42], Iran [43], Morocco [44], Lebanon [45], and Turkey [44,46]. This study updates the knowledge obtained from other studies in the region; yet, it includes samples from mixed populations and correlates the findings to clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%